Tendências tecnológicas 2021 da OMPI, resumo executivo - tecnologia assistiva. (Organizaçô Mundial da Propriedade Intelectual, 2021)
"This groundbreaking report looks at patenting and technology trends in innovation in assistive technology. It identifies the prominent technologies, top players and markets for patent protection across seven domains - mobility, cognition, communication, hearing, the built environment, self-care and vision. Using a scale of technology readiness, it reveals which of the identified assistive products filed for patent protection are closest to commercialization."--